ЕКОНОМІЧНА БЕЗПЕКА РЕГІОНУ В КОНТЕКСТІ ЙОГО ПОЗИЦІОНУВАННЯ - Gricishen, D.O.; Kuchmenko, V.O.; Zablodska, D.V. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2021)
The article summarizes scientific approaches to the economic security of the region in the context of its positioning. The key risks of economic security of the Ukrainian regions have been identified as well as the most important criteria for regions positioning: the gross regional product (GRP) structure, the volume and rates of industrial development, the volume and dynamics of investments; natural resource production and scientific and technical potential; resource efficiency; competitiveness of the region's economy; unemployment rate; the quality of life, the degree of income differentiation, the provision of the population with material benefits and services; energy dependence; integration into the national economy etc. It is noted that the main problem of economic security is to ensure effective management of regional policy, as well as the evaluation of the regions positioning in the context of economic security can be carried out in the main directions: the level of poverty and unemployment in the region; the quality of life of the population; demographic component of the socio-economic security of the region; the ability of the region's economy to sustainably grow; stability of the region's financial system; support of the scientific potential of the region; dependence of the region's economy on imports of the most important types of products; relations of the region with the countries of the European Union. The modern positioning of some security sectors and the consequences of such positioning have been characterized. A system of main indicators has been formed that allows to quantify the level of economic security of the region in the context of its positioning. The methodical approach to evaluating the economic security of a region in the context of its positioning is highlighted. It is noted that despite the goals that are taken into account when positioning the region, the whole process can be structured into the following blocks: organizational and analytical support; methodical and informational support; conceptual software. The article presents the functional components of the mechanism for ensuring the economic security of regions in the context of their positioning. It has been proved that the effective functioning of the mechanism for ensuring the economic security of regions in the context of their positioning requires the effective functioning of all subjects synchronously, which made it possible to formulate a synergistic effect in a formalized form. REFERENCES